Anterior Cruciate Ligament Injury, Return to Play, and Reinjury in the Elite Collegiate Athlete: Analysis of an NCAA Division I Cohort. (July 2014) - Kamath, Ganesh V.; Murphy, Timothy; Creighton, R. Alexander; Viradia, Neal; Taft, Timothy N.; Spang, Jeffrey T.
Background: Graft survivorship, reinjury rates, and career length are poorly understood after anterior cruciate ligament (ACL) reconstruction in the elite collegiate athlete. The purpose of this study was to examine the outcomes of ACL reconstruction in a National Collegiate Athletic Association (NCAA) Division I athlete cohort. Study Design: Case series; Level of evidence, 4. Methods: A retrospective chart review was performed of all Division I athletes at a single public university from 2000 to 2009 until completion of eligibility. Athletes were separated into 2 cohorts: those who underwent precollegiate ACL reconstruction (PC group) and those who underwent intracollegiate reconstruction (IC group). Graft survivorship, reoperation rates, and career length information were collected. Results: Thirty-five athletes were identified with precollegiate reconstruction and 54 with intracollegiate reconstruction. The PC group had a 17.1% injury rate with the original graft, with a 20.0% rate of a contralateral ACL injury. For the IC group, the reinjury rates were 1.9% with an ACL graft, with an 11.1% rate of a contralateral ACL injury after intracollegiate ACL reconstruction. The athletes in the PC group used 78% of their total eligibility (average, 3.11 years). The athletes in the IC group used an average of 77% of their remaining NCAA eligibility; 88.3% of those in the IC group played an additional non-redshirt year after their injury. The reoperation rate for the PC group was 51.4% and was 20.4% for the IC group. Conclusion: Reoperation and reinjury rates are high after ACL reconstruction in the Division I athlete. Precollegiate ACL reconstruction is associated with a very high (37.1%) rate of repeat ACL reinjuries to the graft or opposite knee. The majority of athletes are able to return to play after successful reconstruction.